2015
DOI: 10.1021/acs.jnatprod.5b00252
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids from Pandanus amaryllifolius: Isolation and Their Plausible Biosynthetic Formation

Abstract: Pandanus amaryllifolius Roxb. (Pandanaceae) is used as a flavor and in folk medicine in Southeast Asia. The ethanolic crude extract of the aerial parts of P. amaryllifolius exhibited antioxidant, antibiofilm, and anti-inflammatory activities in previous studies. In the current investigation, the purification of the ethanolic extract yielded nine new compounds, including N-acetylnorpandamarilactonines A (1) and B (2); pandalizines A (3) and B (4); pandanmenyamine (5); pandamarilactones 2 (6) and 3 (7), and 5(E)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…Pandanamine was originally isolated from the leaves of Pandanus amaryllifolius Roxb. (Pandanaceae) (Takayama et al 2001) and was shown to be accompanied by a series of closely related derivatives (Greger 2006) collectively called Pandanus alkaloids (Tsai et al 2015).…”
mentioning
confidence: 99%
“…Pandanamine was originally isolated from the leaves of Pandanus amaryllifolius Roxb. (Pandanaceae) (Takayama et al 2001) and was shown to be accompanied by a series of closely related derivatives (Greger 2006) collectively called Pandanus alkaloids (Tsai et al 2015).…”
mentioning
confidence: 99%
“…Finally, the synthesis of both pandalizine A and B ( 8 and 9 ; Scheme ) was accomplished. These natural alkaloids have only just very recently been isolated from the medicinal plant Pandanus amaryllifolius Roxb . Here, the substrate for the photooxygenation was the meta ‐methyl substituted furylalkylamine 1 h which was directly converted to the indolizidine 3 h (not shown).…”
Section: Methodsmentioning
confidence: 97%
“…[26] Here,t he substrate for the photooxygenation was the meta-methyl substituted furylalkylamine 1h which was directly converted to the indolizidine 3h (not shown). Finally, the synthesis of both pandalizine Aand B(8 and 9;Scheme 6) was accomplished.…”
Section: Methodsmentioning
confidence: 99%
“…These natural alkaloids have only just very recently been isolated from the medicinal plant Pandanus amaryllifolius Roxb. [26] Here,t he substrate for the photooxygenation was the meta-methyl substituted furylalkylamine 1h which was directly converted to the indolizidine 3h (not shown). Theisolation report suggests that 3his the biogenetic precursor to pandalizines Aand B, [26] and indeed, the natural products could be obtained upon addition of TFAinCHCl 3 or MeOH, respectively,a st he culmination of the one-pot process (68 %o verall isolated yield for pandalizine Aa nd 61 %f or pandalizine B).…”
mentioning
confidence: 99%